2006
DOI: 10.1097/01.ccm.0000214516.73076.82
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oropharyngeal decontamination by povidone-iodine on ventilator-associated pneumonia in patients with head trauma*

Abstract: The regular administration of povidone-iodine may be an effective strategy for decreasing the prevalence of ventilator-associated pneumonia in patients with severe head trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 37 publications
(68 reference statements)
2
64
0
6
Order By: Relevance
“…Providoneiodine and iseganan have only been evaluated in one trial each. The providone-iodine trial showed a decrease in VAP rates but no impact on patient outcomes [62]. The trial of iseganan showed no impact on either VAP rates or patient outcomes [63].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%
“…Providoneiodine and iseganan have only been evaluated in one trial each. The providone-iodine trial showed a decrease in VAP rates but no impact on patient outcomes [62]. The trial of iseganan showed no impact on either VAP rates or patient outcomes [63].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%
“…For example, chlorhexidine is employed because of its high level of antibacterial, antiviral, and antifun-gal activities and high substantivity (ability to bind to oral tissues with subsequent slow release of antiseptic properties and therefore a long period of antibacterial action). 8,9 Although generally safe, chlorhexidine is not free of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Antiseptik yang sering digunakan adalah povidone iodine dan chorhexidine. Seguin (2006) meneliti 98 klien trauma kepala dengan Glasgow Coma Score ≤8 dan ventilator ≥2 hari. Sample dibagi dalam 3 kelompok yaitu povidone iodine n=36, saline group n=31 dan kelompok kontrol n=31, menyimpulkan bahwa povidone iodine sebagai strategi yang efektif untuk menurunkan prevalensi ventilator-associated pneumonia (VAP) pada klien tauma kepala berat.…”
Section: Komponen Kekebalanunclassified